The Cardio- and Neuroprotective Effects of Corvitin and 2-Oxoglutarate in Rats with Pituitrin-Isoproterenol-Induced Myocardial Damage - V. Tkachenko; Y. Kovalchuk; N. Bondarenko; О. Bondarenko; G. Ushakova; A. Shevtsova (Biochemistry Research International)
Heart diseases, especially acute coronary syndrome (ACS), are among the most severe illnesses that often lead to death. Despite significant advances in the prevention and treatment of ACS, the incidence of the disease and its complications are very serious. The imbalance between pro- and antioxidant systems, the formation of active carbonyl compounds, and the end products of glycation in the blood and tissues are the key moments in the development of heart and neurological disorders leading to a change of behavioral responses. So, the search for antioxidants with cardio- and neuroprotective effects is an urgent task. This study was aimed at evaluating the effects of Corvitin and 2-oxoglutarate on physiological parameters, heart histology, and markers of carbonyl/oxidative stress of rats with pituitrin-isoproterenol-induced myocardial damage (PIMD). Increased sweating, tachycardia, significantly decreased locomotor and exploratory activity, changes of ECG, heart histology, and biochemical changes were observed in the PIMD-group. The administration of Corvitin or 2-OG led to the recovery of locomotor and cognitive activities of the rats, improvement in heart histology, a decrease in the levels of thiobarbituric acid reactive substances, advanced glycated end products, and various changes in the activity of the antioxidant enzymes, 6 days after PIMD. So, Corvitin and exogenous 2-OG show cardio- and neuroprotective effects through the decrease of carbonyl/oxidative stress and regulation of the activity of the antioxidant system.